Systematic Review: Developing Sports Tourism for Sustainable Economic Development - Gharibpoor, Keivan; safari, Leila; Nasiri Farsani, Mokhtar; Majedi, Nima (AI and Tech in Behavioral and Social Sciences, 2024)
Sports tourism presents an innovative pathway for sustainable economic growth, intertwining the excitement of sports with the expansiveness of the tourism industry. This review synthesizes current research on developing sports tourism with a focus on enhancing economic sustainability, aiming to offer actionable insights and a robust framework for practitioners and policymakers. The methodology for this systematic review involved a comprehensive search of databases including PubMed, Scopus, Web of science and Google Scholar for studies published in the last ten years. Keywords such as "sports tourism", "sustainable economic development", "tourism development models", and "community-based sports tourism" were used. Studies were screened based on relevance to sports tourism development and sustainability. The inclusion criteria encompassed peer-reviewed articles, government reports, and case studies that discuss the implementation, outcomes, and challenges of sports tourism initiatives aimed at sustainable development. The review identified significant elements contributing to the successful integration of sports tourism into local economic development plans. These include community involvement, strategic location selection, infrastructure investment, and environmental management strategies. Best practice case studies were analyzed to illustrate these elements in action, highlighting the role of policy alignment and stakeholder engagement in fostering sustainable outcomes. Sports tourism offers substantial opportunities for sustainable economic enhancement if strategic, community-focused approaches are employed. Key recommendations for development include leveraging local sports culture, prioritizing environmental sustainability, and enhancing stakeholder collaboration. The review provides a foundational model for developing sports tourism that aligns with broader economic sustainability goals, recommending further empirical studies to refine and adapt the model to diverse geographical contexts.